Uncertainty Estimation of the Fe Content Measurement in the Clean Water Using UV- Vis Spectrophotometer - Adi Syahputra (Stannum : Jurnal Sains dan Terapan Kimia, 2019)
Good laboratories should be able to apply procedures uncertainty for measuring of both conventional and instrument equipment. As well as the testing for Fe content using UV-Vis Spectrophotometer. As for the purpose for calculating the uncertainty estimated to determine the range of values within which estimated the true value of the testing standard solution Fe using UV-Vis Spectrophotometer. The uncertainty estimation are influenced by several factors such as sample used, reading of spectrophotometer, repeatability, sample volume. The uncertainty of the calculation obtained a value of ± 0,02 mg/L. Further testing of Fe content in the clean water using UV-Vis Spectrophotometer at the 500 nm wavelength which forms an orange solution as indication of Fe content in the water. The result of Fe content has quality standards according to the spesifications issued by ministry of health Republic of Indonesia in 2010 for drinking water.